2018
DOI: 10.1016/j.jaip.2017.12.039
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life with Subcutaneous C1-Inhibitor for Prevention of Attacks of Hereditary Angioedema

Abstract: In patients with frequent HAE attacks, a treatment strategy of routine prevention with self-administered twice weekly C1-INH(SC) had a greater impact on improving multiple HAE-related HRQoL impairments, most notably anxiety and work productivity, compared with on-demand treatment alone (placebo prophylaxis).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
67
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 74 publications
(80 citation statements)
references
References 47 publications
7
67
0
6
Order By: Relevance
“…It was hard for her to take care of the family, and she had difficulty attending school. After the disease was controlled, she was able to live her life fully, in accordance to the study of Lumry et al 7. The Lumry et al study showed that administrating subcutaneous C1-INH can improve many aspects of the burden of HAE such as anxiety, work productivity and activity impairment.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…It was hard for her to take care of the family, and she had difficulty attending school. After the disease was controlled, she was able to live her life fully, in accordance to the study of Lumry et al 7. The Lumry et al study showed that administrating subcutaneous C1-INH can improve many aspects of the burden of HAE such as anxiety, work productivity and activity impairment.…”
Section: Discussionsupporting
confidence: 72%
“…Low values should be repeated to confirm the diagnosis 6. HAE can have severe impact on various aspects of health-related quality of life, because the disease is lifelong, unpredictable and debilitating 7. Untreated angioedema of the larynx is associated with a high mortality rate where fatal events may occur within 10 min to 14.3 hours 8.…”
Section: Introductionmentioning
confidence: 99%
“… 11 , 15 – 21 Study findings based on the European Quality of Life-5 Dimensions Questionnaire (EQ-5D) reveal that HAE attacks have a marked impact on perceived health status. As shown in Figure 2 , 16 , 20 , 22 – 28 EQ-5D scores reflecting HRQoL during an HAE attack, as reported in a study conducted in Denmark, Germany, and Sweden, ranged from 0.08 during a severely painful attack to 0.61 during an attack with mild pain (1 = full health). Even between HAE attacks, the mean EQ-5D scores reflected impairment (0.72).…”
mentioning
confidence: 72%
“…18 In a post hoc analysis of all patients randomized in the OLE (n = 90), Lumry et al reported on the benefit of C1INH (SC) of various patient-reported outcome QoL measures related to the burden of HAE such as clinically meaningful improvements in anxiety and depression scores, improved work productivity, and less nonwork activity impairment, as well as high treatment satisfaction and perceived effectiveness compared with on-demand treatment alone. 19 The frequency, severity, and location of attacks are major factors associated with negative QoL in children with HAE. 7 The inability to attend school and decreased involvement in social activities, as well as physical impairment result in reduced QoL of pediatric patients.…”
Section: Discussionmentioning
confidence: 99%